POINTING OUT THE NEED FOR TIMELY SUBMISSION OF THE PROPOSAL FOR OPENING THE BANKRUPTCY PROCEDURE (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
AbstractIn this paper, special attention will be paid to the importance of timely initiation ofbankruptcy proceedings, ie the need for an efficient bankruptcy system which is a necessarypart of the market economy of each country, as it provides security to creditors, recovery ofcompanies with financial difficulties. The paper will explain the reasons that affect the delayand inefficiency of the bankruptcy procedure. On the other hand, the paper will explain thebenefits of timely and efficient implementation of the bankruptcy procedure, whose mainpurpose is to satisfy the interests of all those who participate in it. Therefore, I will cover thespecial role of the Bankruptcy Trustee, which is especially evident after the legal consequencesof the opening of the Bankruptcy procedure, where it protects the interests of the creditors andthe bankruptcy debtor. Here, I will especially cover his special role as an authorized proposerin relation to filing a lawsuit for damages, ie damage suffered by creditors due to irresponsiblebehavior of the bankruptcy debtor, ie failure to file a proposal to open bankruptcy proceedings,which led to reduction of the bankruptcy estate from which the creditors are settled. The subjectof research is the timely initiation and completion of the bankruptcy procedure in our law, asa procedure conducted by the Bankruptcy Trustee who is a professional in it. Meanwhile, thepurpose of the research is to identify the disadvantages and advantages regarding the legalorder of the bankruptcy procedure in terms of the responsibility of the management bodies fornot submitting the proposal for opening the bankruptcy procedure.